(3QSGdI aj Yde GdCcSjQs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3ajfeG jYQa eYGQVI (B((3eaGhVI(B) (3hGdJeS ef JYQja Pdc ai LRA djchf JPcQI s
(3BNQgG (B:s
(3GdCQV hdGdCHjV Ke KdGKI djS ajgG GdfGOi hGdCUaQ s
(3Vef eLehY s
(3hgj QSGdI GHf SjfG Edi GdTjN CHj GdMSf Sgd Hf eMeO GdSgjdjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdadSaI hGdefWbs